2019
DOI: 10.1063/1.5086105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity in molecular orbital energy predictions with kernel ridge regression

Abstract: Instant machine learning predictions of molecular properties are desirable for materials design, but the predictive power of the methodology is mainly tested on well-known benchmark datasets. Here, we investigate the performance of machine learning with kernel ridge regression (KRR) for the prediction of molecular orbital energies on three large datasets: the standard QM9 small organic molecules set, amino acid and dipeptide conformers, and organic crystal-forming molecules extracted from the Cambridge Structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 71 publications
3
112
0
Order By: Relevance
“…[17] Supervised learning applies in situations where a machine learning model is trained on input-output pairs from a real process to produce optimal outputs for unseen inputs. Typical applications are predictions of physical properties (like formation energies [200][201][202] or molecular properties [203][204][205][206][207] ) given the input features of a material or process (e.g., geometry, physical properties, external conditions).…”
Section: Introduction To Machine Learningmentioning
confidence: 99%
“…[17] Supervised learning applies in situations where a machine learning model is trained on input-output pairs from a real process to produce optimal outputs for unseen inputs. Typical applications are predictions of physical properties (like formation energies [200][201][202] or molecular properties [203][204][205][206][207] ) given the input features of a material or process (e.g., geometry, physical properties, external conditions).…”
Section: Introduction To Machine Learningmentioning
confidence: 99%
“…[33][34][35] Our study indicated that this machine-learning strategies may provide OFET researchers supporting details to fine-tune the electronic structure and thus the charge transport property of the n-type organic materials. [33][34][35] Our study indicated that this machine-learning strategies may provide OFET researchers supporting details to fine-tune the electronic structure and thus the charge transport property of the n-type organic materials.…”
mentioning
confidence: 77%
“…dictions for solids [5][6][7][8], accelerated molecular property prediction [9][10][11], creation of new force-fields based on quantum mechanical training data [12][13][14][15][16][17][18][19], search for catalytically active sites in nanoclusters [20][21][22][23][24] and efficient optimization of complex structures [25][26][27]. Atomistic machine learning establishes a relationship between the atomic structure of a system and its properties.…”
Section: Introductionmentioning
confidence: 99%